Why do slot machine gamblers use stopping devices? Findings from a 'Casino Lab' experiment. Issue 2 (4th May 2018) - Chu, Stephanie; Limbrick-Oldfield, Eve H.; Murch, W. Spencer; Clark, Luke
ABSTRACT: Stopping devices are a structural characteristic of modern slot machines that enable the player to brake the spinning reels manually, but with no influence on the predetermined outcome. This study tested two mechanisms for why players might use a stopping device: (1) enhanced 'illusory control', and (2) faster game speed. Thirty student participants and 31 past-year slot machine gamblers played a multi-line slot machine equipped with a stop button, situated in a laboratory environment. During 20 minutes of play, participants could use the stop button as often as they wished. Contrary to predictions, the Gamblers' Beliefs Questionnaire (GBQ), a trait measure of illusion of control, did not predict stop button usage. Participants who did and did not endorse the stop button as effective did not differ in their actual use of the device. Stop button use was associated with faster spin initiation latencies, and specifically increased following spins on which the use of the stop button coincided with a win. The data are interpreted as more consistent with a low-level operant conditioning account of slot machine gambling than a higher-level account based on cognitive distortions. By increasing speed of play, stopping devices may increase gambling losses and exaggerate gambling-related harms.